Analisis Penerapan Pencatatan Keuangan Berbasis SAK EMKM Pada Usaha Mikro Kecil Menengah (UMKM) Ai Your Lash Beauty Salon Kota Metro - Sapta Prasanti; Nedi Hendri; Angga Kurniawan (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the Application of SAK EMKM-Based Financial Recording in Micro, Small and Medium Enterprises (MSMEs) Ai Your Lash Beauty Salon Metro City. The data were obtained from the results of written data and salon financial recording reports and interview results. Analysis of the research data was carried out using descriptive analysis. The results of this study indicate that UMKM Ai Your Lash Beauty Salon Kota Metro does not record its business financial statements in accordance with SAK EMKM because there is no supervision from parties who have an interest in the financial reports of MSME stakeholders, namely from the government, related institutions and regulators.